Manajemen Kepala Sekolah Dalam Meningkatkan Kedisiplinan Guru Di Sd Negeri Kalenpandan Pamulihan - Abdul Rosyid; Muhamad Ripin Ikwandi (EDUSIANA Jurnal Manajemen dan Pendidikan Islam, 2024)
This research discusses the management of school principals in the SD Negeri Kalenpandan Pamulihan Brebes which is one of the educational institutions that are superior and trusted by the community. School management is a factor and the key to the success of the school, including in improving teacher discipline. Therefore, this research is focused on principal management in improving teacher discipline. This study aims to determine the management of the principal which includes planning, organizing, implementing, supervising or evaluating in improving teacher discipline at SD Negeri Kalenpandan Pamulihan Brebes. This research is a qualitative descriptive research, which was conducted at SD Negeri Kalenpandan Pamulihan Brebes using a case study plan. The data collection techniques used include: 1). Observation (Observation), 2). Interview 3). Documentation. The results of this study can show that: 1). Principal planning carried out at SD Negeri Kalenpandan Pamulihan Brebes in improving teacher discipline includes: a). Planning rules b). Teacher performance planning c). Guidance and direction planning. This planning is carried out in order to discipline the teacher in the morning apple, come to school, and enter teaching hours 2). Organizing principals in improving teacher discipline by holding teacher coaching once every month. 3). The implementation of the principal in improving teacher discipline is to form cooperation with teachers, provide direct direction, and provide opportunities and opportunities for teachers to improve performance professionalism. 4). Evaluation of the principal in improving teacher discipline is seen from the teacher's development in implementing discipline in the school is already running or not, which will then be evaluated in a meeting with the teacher. Keywords: Principal Management, Teacher Discipline